FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU TIDAK AMAN (UNSAFE ACTION) PADA PEKERJA WORKSHOP PT MAJU SELARAS INSTRUMINDO - Alfarisie, Muhammad Salman; Kurniawan, Deni (Fakultas Teknik - Universitas Satya Negara Indonesia, 2024)
The aim of the research is to find out and describe factors related to unsafe action in workshop workers. The research was conducted at PT Maju Selaras Instrumindo, Gang Alun RW 002 Larangan District, Tangerang City, Banten. The research was conducted at PT Maju Selaras Instrumindo, Alun Alun RW 002, Larangan District, Tangerang City, Banten. The research was conducted from April to July 2023. The research used a quantitative descriptive method, with a research design using cross-sectional observations. The population of this research is all workshop workers at PT Maju Selaras Instrumindo in 2023. The sampling technique uses saturated sampling. The research sample is 15 workshop workers. Data analysis was performed to test the hypothesis by conducting univariate analysis and bivariate analysis using the Chi-Square test. The results of the univariate analysis research show that knowledge about K3 is predominantly in the good category. Compliance with the use of PPE is dominated by the obedient category. Unsafe action is in the less risky category. From the research findings, it can be concluded that: (1) There is a relationship between knowledge about K3 and unsafe action. This means that the more knowledge about K3 increases, the lower the incidence of unsafe action. (2) There is a relationship between compliance with the use of PPE and unsafe action. This means that the more compliance with the use of PPE increases, the lower the incidence of unsafe action.